STRESS MANAGEMENT EVALUATION OF DIPLOMA 3 AIR TRAFFIC CADETS IN AIR TRAFFIC CONTROL SIMULATION AT SURABAYA AVIATION POLYTECHNIC - Nurjanah, Aisya; Bahrawi, Ahmad; Dewi Kusumayati, Lusiana (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The Air Traffic Controller (ATC) profession is known for its high-stress environment due to the demands of making quick and accurate decisions under pressure. Diploma 3 Air Traffic Management students at Politeknik Penerbangan Surabaya, although still in training, experience similar conditions during complex and high-pressure ATC simulations. Poorly managed stress can affect concentration, decision-making, and overall learning effectiveness. Therefore, this study aims to evaluate the stress management of students during ATC simulations and provide recommendations for improving the training program. This study employed a qualitative descriptive method with data collected through observation, semi-structured interviews, and documentation. The research subjects were active students participating in ATC simulations, while the research objects included stress symptoms, coping strategies used, and the effectiveness of stress management. Data analysis followed the stages of reduction, presentation, and conclusion drawing, with source and method triangulation to ensure data validity. The findings indicate that the primary sources of stress are time pressure, air traffic complexity, and fear of making mistakes in front of instructors. Students employed stress management strategies such as deep breathing techniques, positive affirmations, short breaks, and seeking support from instructors and peers. However, stress management was not yet optimal under high-pressure simulation conditions. It is recommended to integrate systematic stress management training and gradually increase simulation scenario difficulty to strengthen students’ mental readiness.